2017
DOI: 10.17957/tpmj/17.4001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ischaemia and Stroke; Role of Carotid Doppler

Abstract: ABSTRACT… Introduction: Colour Doppler sonography is a well-established widely available, noninvasive, cost effective and a reliable method for assessing cerebrovascular circulation. It has become a valuable completion of the sonographic workup in patients with cerebral ischaemia and infarction. Its accuracy is close to angiography. Objectives: To determine the frequency of significant carotid artery stenosis in patients of cerebral ischaemia/stroke and its characterized sonographic appearance of plaque. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…It was almost similar 68% in the previous Nepalese study by Pathak et al 8 In our current study, the mean age of subjects with ischemic stroke was 64±13.4 years with majority of cases in age group of 51-70 years of age with male predominance (M:F= 3: 2). The mean age of the patients was 61, 60.5, and 52 years with male dominance in an earlier study by Pathak et al 8 , Syed et al 9 , and Khan et al 10 In the studies by Fernandes et al 11 and Chamarthi et al 12 , the highest incidence of stroke was found in the male population in the age group of 51-70 years; findings consistent to our study. However, maximum number of patients belonged to even younger age group of 51-60 years according to Haq et al1 3 About 7.5% were young stroke patients, aged <40 years in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It was almost similar 68% in the previous Nepalese study by Pathak et al 8 In our current study, the mean age of subjects with ischemic stroke was 64±13.4 years with majority of cases in age group of 51-70 years of age with male predominance (M:F= 3: 2). The mean age of the patients was 61, 60.5, and 52 years with male dominance in an earlier study by Pathak et al 8 , Syed et al 9 , and Khan et al 10 In the studies by Fernandes et al 11 and Chamarthi et al 12 , the highest incidence of stroke was found in the male population in the age group of 51-70 years; findings consistent to our study. However, maximum number of patients belonged to even younger age group of 51-60 years according to Haq et al1 3 About 7.5% were young stroke patients, aged <40 years in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Significant ICA stenoses >50 % was observed in 24.2% patients with ischemic stroke in the current study. Similar (28%) was the finding by Bharathi et al15 It was however, lower (12%) according to Chamarthi et al12 ICA stenoses>50% was observed higher (43% and 45.1%) in the studies by Khan et al10 and Bollipo et al14 respectively. Near total occlusion was seen in 2.5% of the patients while none of the patients had a complete occlusion in the current study.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, the comorbidity of coronary and carotid artery disease should be evaluated in detail during the preoperative period. Khan et al [21] reported that color Doppler sonography is nowadays the first imaging examination performed for the diagnosis of carotid artery stenosis. Its dual ability to evaluate both morphologic and hemodynamic abnormalities and its cost-effectiveness make color Doppler ultrasound the only test applied before a therapeutic decision [21] .…”
Section: Discussionmentioning
confidence: 99%